An Analysis of Translation Techniques of Modality in Hortatory Text by English Department Students of UNP - Yogi Ilham; Witri Oktavia (Universitas Negeri Padang, 2020)
This study analyzes the translation technique of modality in hortatory text and translation accuracy of hortatory text made by the students in academic year 2017 at the English Language and Literature Department. The purpose of this research is to find out the translation techniques used in translation of modality in hortatory text and translation accuracy in translating hortatory text entitled